The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5505/1304.7361.2011.70298
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumothorax Treatment Modalities: A Study of 48 Cases

Abstract: ÖZET AmaçSpontan pnömotoraks akciğer ile göğüs duvarı arasında serbest hava toplanmasıdır. Tanısı klinik ve/veya radyolojik olarak konur. Tedavi yaklaşımları açısından farklı uygulamalar mevcuttur. Bu ça-lışmada, pnömotoraks ve tedavi seçenekleri üzerindeki klinik tecrü-belerimizi literatür bilgileri eşliğinde tartıştık. Gereç ve YöntemKliniğimize başvuran 48 spontan pnömotoraks olgusu prospektif olarak değerlendirildi. Çalışmamıza primer spontan pnömotoraks olguları dahil edildi. Olgular yaş, cinsiyet, ek has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Smoking has been reported as a risk factor for SPT [21]. A study evaluating SPT cases in the emergency department, it was reported that 71.7% of the patients had a history of smoking but this was not statistically significant [11].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been reported as a risk factor for SPT [21]. A study evaluating SPT cases in the emergency department, it was reported that 71.7% of the patients had a history of smoking but this was not statistically significant [11].…”
Section: Discussionmentioning
confidence: 99%